2020
DOI: 10.1016/j.immuni.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Immune Profiling of Human Gut-Associated Lymphoid Tissue Identifies a Role for Isolated Lymphoid Follicles in Priming of Region-Specific Immunity

Abstract: Highlights d Novel methods for isolating human M-ILFs, SM-ILFs, and GALT-free intestinal LP d Human M-ILFs and SM-ILFs are highly organized sites of adaptive immune induction d An adaptive immune roadmap of human GALT and GALTfree LP d Human ILFs contribute to regionalized adaptive immune responses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
138
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(140 citation statements)
references
References 62 publications
(98 reference statements)
1
138
1
Order By: Relevance
“…It is important to note, however, that, based on data from the blood, the functionality of these cells is likely to be impaired (24,54). Further studies with larger numbers of healthy participants (e.g., subjects consenting to research biopsies) will be needed to explore in more depth the impact of HIV infection on unconventional T-cells in the different tissue compartments and to investigate potential distinctions between the lamina propria and intraepithelial intestinal tissue compartments (55).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that, based on data from the blood, the functionality of these cells is likely to be impaired (24,54). Further studies with larger numbers of healthy participants (e.g., subjects consenting to research biopsies) will be needed to explore in more depth the impact of HIV infection on unconventional T-cells in the different tissue compartments and to investigate potential distinctions between the lamina propria and intraepithelial intestinal tissue compartments (55).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of bacteria interact indirectly with intestinal epithelial cells, mediated by food-fermented postbiotics [ 114 , 115 ]. The mucosa also serves as a source of nutrients for commensal bacteria, such as Akkermansia muciniphila , while changes in the microbiome community, mainly the ratio of Bacteroides to Firmicutes , could alter mucin glycosylation [ 116 , 117 , 118 ]. In a heathy status, gut microbiota is restricted to the outer layer of mucosa, stimulating active B cells to secrete secretory IgA (sIgA), while promoting goblet cells to produce MUC2 [ 119 ].…”
Section: Intestinal Microbiota and Ibdmentioning
confidence: 99%
“…Compared with the cecum, IgA + plasma cells of the sigmoid colon respond to a rich and unevenly represented community of bacterial species; most likely accounting for the increased activation, migratory and greater clonality status of plasma cells ( 143 ). Indeed, by means of a novel method for identifying and isolating lymphoid follicles along the length of the human intestine and IgA sequencing analysis, Agace’s group showed that IgA adaptive immune responses are initiated in an anatomically restricted manner in the human Peyer’s patches and submucosal isolated lymphoid follicules contributing to the ileal and colonic plasma cell repertoires, respectively ( 152 ).…”
Section: The Gut Microbiome and The Intestinal Immune Systemmentioning
confidence: 99%